Cleaning Interactions Between Crows and Sika Deer: Implications for Tick‐Borne Disease Management - Kanzi M. Tomita; Hiroyuki Matsuyama (Ecology and Evolution, 2025)
ABSTRACT Cleaning interactions between mammals and birds have been widely observed worldwide. Here, we report cleaning interactions between sika deer and crows in Japan, based on a field observations using camera traps and online research. Online research was performed on social media platforms such as X (formerly Twitter), YouTube, and personal blogs. We finally collected 27 cases of cleaning associations between sika deer and crows. Crows associated with male more than female deer and mainly pecked their heads or necks, suggesting that crows remove Ixodid ticks from the deer's surface. Given that ticks on sika deer are vectors of several zoonotic pathogens such as Rickettsia and Borrelia spp., further studies should be conducted to examine the roles of crows as biocontrol agents of ticks and tick‐borne diseases.